Optimizing soil organic carbon stock assessments for spekboom reforestation of degraded lands in the Eastern Cape, South Africa - Rheeder, Paul Johan (Stellenbosch : Stellenbosch University, 2025)
Thesis (MScAgric)--Stellenbosch University, 2025.